2002
DOI: 10.1046/j.1365-2672.2002.01704.x
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of colonic bacteria and volatile fatty acid production by dietary high amylose maize (amylomaize) starch granules

Abstract: Aims: To study the effects of amylomaize starch and modified (carboxymethylated and acetylated) amylomaize starches on the composition of colonic bacteria and the production of volatile fatty acids, in mice. Methods and Results: Balb ⁄ c mice were fed with experimental diets containing various amount of amylomaize and modified amylomaize starches. Colonic bacterial populations and short-chain fatty acids were monitored. Results showed that the increases in indigenous bifidobacteria were detected in mice fed al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(60 citation statements)
references
References 27 publications
3
57
0
Order By: Relevance
“…These observations suggest that the intestinal microbiota were changed by the administration of HAS and CBM588. It is known that the fecal number of Bifidobacterium increases when HAS is fed to pigs (5) and mice (48). However, there are very few bacterial strains that can utilize HAS, although there are many kinds of bacterial species that can utilize amylopectin maize starch (49).…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that the intestinal microbiota were changed by the administration of HAS and CBM588. It is known that the fecal number of Bifidobacterium increases when HAS is fed to pigs (5) and mice (48). However, there are very few bacterial strains that can utilize HAS, although there are many kinds of bacterial species that can utilize amylopectin maize starch (49).…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not determine gastrointestinal microbial activity in the current study, prebiotic effects have been reported after 2 -4 weeks of daily RS intake of between 15 and 55 g (38-42), thus it is likely the RS intake in the current study had a similar effect. Resistant starch specifically stimulates the growth of bifidobacteria in the 13 colon (15,43) and increases caecal lactobacilli and bifidobacteria levels in human flora-associated rats (16). Bifidobacteria can hydrolyze daidzin and genistin from soy milk to their respective aglycones (44) and metabolize daidzein in human faecal samples (45,46) and these effects have been attributed to its β-glucosidase activity (36,44).…”
mentioning
confidence: 99%
“…SCFAs are one of the most essential microbial products affecting a number of physiological processes such as energy utilization, host-microbe signaling, production of secondary bile acids, control of colonic pH, and gut motility. In addition, SCFAs play a role in epithelial cell proliferation and are associated with reduced diet-induced DNA damage and decreased precancerous lesions [30]. SCFAs are metabolized rapidly by the colon epithelial cells, referred to a colonocytes, which line the villi of the colon.…”
Section: Short Chain Fatty Acidsmentioning
confidence: 99%